Sobre el Derecho Procesal en el siglo XXI - Peñaranda Valbuena, Héctor Enrique; Quintero de Peñaranda, Olga; Peñaranda Quintero, Héctor Ramón; Peñaranda, Mercedes (Nómadas. Critical Journal of Social and Juridical Science, 2011)
The education of the Procedural Right in the 21st century has caused that in the doctrine a great number of authors feels motivated to study, mainly, the reasons that argue the necessity that a common doctrine around this branch of the Right exists, useful from the scientific and pedagogical point of view, formulating the concepts computers of the different processes. Of the exposed thing previously we considered of integral way that this discipline is defined as the science that studies and regulates the coordinated activity of the judge and the parts with the purpose of to solve the legal conflicts among them, by means of the application of the norms of Right. Being its fundamental function not only to serve but effective doing the material right.
Keywords: process; law; procedural